LPA1 receptor–mediated thromboxane A2 release is responsible for lysophosphatidic acid‐induced vascular smooth muscle contraction. Issue 4 (18th January 2017) - Dancs, Péter Tibor; Ruisanchez, Éva; Balogh, Andrea; Panta, Cecília Rita; Miklós, Zsuzsanna; Nüsing, Rolf M.; Aoki, Junken; Chun, Jerold; Offermanns, Stefan; Tigyi, Gábor; Benyó, Zoltán
Abstract : Lysophosphatidic acid (LPA) has been recognized recently as an endothelium‐dependent vasodilator, but several lines of evidence indicate that it may also stimulate vascular smooth muscle cells (VSMCs), thereby contributing to vasoregulation and remodeling. In the present study, mRNA expression of all 6 LPA receptor genes was detected in murine aortic VSMCs, with the highest levels of LPA1, LPA2, LPA4, and LPA6 . In endothelium‐denuded thoracic aorta (TA) and abdominal aorta (AA) segments, 1‐oleoyl‐LPA and the LPA1–3 agonist VPC31143 induced dose‐dependent vasoconstriction. VPC31143‐induced AA contraction was sensitive to pertussis toxin (PTX), the LPA1&3 antagonist Ki16425, and genetic deletion of LPA1 but not that of LPA2 or inhibition of LPA3, by diacylglycerol pyro‐phosphate. Surprisingly, vasoconstriction was also diminished in vessels lacking cyclooxygenase‐1 [COX1 knockout (KO)] or the thromboxane prostanoid (TP) receptor (TP KO). VPC31143 increased thromboxane A2 (TXA2 ) release from TA of wild‐type, TP‐KO, and LPA2 ‐KO mice but not from LPA1 ‐KO or COX1‐KO mice, and PTX blocked this effect. Our findings indicate that LPA causes vasoconstriction in VSMCs, mediated by LPA1 ‐, Gi ‐, and COX1‐dependent autocrine/paracrine TXA2 release and consequent TP activation. We propose that this new‐found interaction between the LPA/LPA1 and TXA2 /TP pathways plays significant roles in vasoregulation, hemostasis, thrombosis, and vascular remodeling. —Dancs, P. T., Ruisanchez, E., Balogh, A., Panta, C. R., Miklós, Z., Nüsing, R. M., Aoki, J., Chun, J., Offermanns, S., Tigyi, G., Benyó, Z. LPA1 receptor‐mediated thromboxane A2 release is responsible for lysophos‐phatidic acid‐induced vascular smooth muscle contraction. FASEB J . 31, 1547–1555 (2017) www.fasebj.org